Age-depth profile from a 2.5D model of the Beyond EPICA ice core drill site at Little Dome C, Antarctica - Ailsa Chung; Frédéric Parrenin; Rob Mulvaney; Luca Vittuari; Massimo Frezzotti; Antonio Zanutta; Marie G P Cavitte; David A Lilien; Olaf Eisen (PANGAEA, 2025)
We used a 2.5D inverse model constrained by radar horizons to find the age-depth profile at the European Beyond EPICA - Oldest Ice project drill site (BELDC; 75.29917 °S, 122.44516 °E) at Little Dome C (LDC), Antarctica. Further details on the model can be found in the associated publication: Chung et al. (2024; doi:10.5194/egusphere-2024-1650). The model constraints were derived from the LDC-VHF radar dataset (Chung et al. 2023; doi:10.5194/tc-17-3461-2023). The radar survey was conducted during the 2019-20 Antarctic field season in a collaboration between the University of Alabama (UA), the University of Copenhagen (CPH) and the Alfred Wegener Institute (AWI), using the Little Dome C-Very High Frequency radar system (LDC-VHF; Chung et al., 2023; doi:10.5194/tc-17-3461-2023). The 2.5D model was applied to a flow line from Dome C to BELDC by Chung et al. (2024; doi:10.5194/egusphere-2024-1650). Here we present the resulting modelled age-depth profile at BELDC. We put the "maximum age" where the age density becomes > 20 ka/m - the threshold for which a paleoclimatic signal can reasonably be extracted. This occurs at 2452 m depth with an age of 1.12 Ma. However, we have chosen to include the entire modelled profile down to the "accreted ice" depth of 2485 m, in case that < 20 ka/m requirement proves to be too stringent. The depth of accreted ice is the deepest point where the model provides physically interpretable results (see Chung et al., 2024 for details).